Модернізація системи стабілізації температури повітря у вулику - Трикула, Максим Сергійович; Trykula, Maksym (ЦНТУ, 2025)
У роботі розглянуто проблематику автоматизації в галузі бджільництва — одній із сфер сільського господарства, що нині не отримує належної уваги в Україні. Це зумовлено тим, що великі аграрні підприємства здебільшого зосереджуються на рослинництві або тваринництві, залишаючи бджільництво поза межами стратегічного розвитку. The paper examines the issue of automation in the beekeeping industry, one of the areas of agriculture that currently does not receive due attention in Ukraine. This is due to the fact that large agricultural enterprises mostly focus on crop production or livestock breeding, leaving beekeeping outside the scope of strategic development.
Modernisation of the air temperature stabilisation system in the hive
Keywords: система стабілізації температури; вулик; temperature stabilization system; hive